Evaluation of Prescription of Cases of Gerd Acid Disorders in Patients at Kasatria Public Health Center, Pematang Siantar City - Beta Hanindiya; Mustaruddin; Doni Saputra Pasaribu; Sekar Pembayun (PT Inovasi Pratama Internasional, 2022)
In the treatment of cases of stomach acid disorders, single therapy is usually used, but there are some who use combination therapy. Usually the drugs used in combination therapy are given based on the severity of stomach acid disorders. From the study it was found that the profile of the use of gastric acid disorders or a combination of drugs was as follows: acid reflux drugs or a combination of many were used in patients with gastritis and dyspepsia, based on age the most widely treated drugs for stomach acid disorders or a combination were the age range of 44-45 years (28%), the administration of drugs for stomach acid disorders or combinations related to clinical symptoms was the most common being dizziness and nausea and the most used was the combination of antacids + Ranitidine + Sucralfate, the duration of administration of drugs for stomach acid disorders or combinations was in the range of less than 7 days and DRP ( Potential Drug Related Problems found are interactions between Omeprazole and Diazepam, Omeprazole and Vitamin B12. There is no administration of drug doses for stomach acid disorders or combinations that exceed the doses suggested by Liberatur.